Subsecond accurate myelin water fraction reconstruction from FAST‐T2 data with 3D UNET. Issue 6 (28th January 2022) - Kim, Jeremy; Nguyen, Thanh D.; Zhang, Jinwei; Gauthier, Susan A.; Marcille, Melanie; Zhang, Hang; Cho, Junghun; Spincemaille, Pascal; Wang, Yi
Abstract : Purpose: To develop a 3D UNET convolutional neural network for rapid extraction of myelin water fraction (MWF) maps from six‐echo fast acquisition with spiral trajectory and T2 ‐prep data and to evaluate its accuracy in comparison with multilayer perceptron (MLP) network. Methods: The MWF maps were extracted from 138 patients with multiple sclerosis using an iterative three‐pool nonlinear least‐squares algorithm (NLLS) without and with spatial regularization (srNLLS), which were used as ground‐truth labels to train, validate, and test UNET and MLP networks as a means to accelerate data fitting. Network testing was performed in 63 patients with multiple sclerosis and a numerically simulated brain phantom at SNR of 200, 100 and 50. Results: Simulations showed that UNET reduced the MWF mean absolute error by 30.1% to 56.4% and 16.8% to 53.6% over the whole brain and by 41.2% to 54.4% and 21.4% to 49.4% over the lesions for predicting srNLLS and NLLS MWF, respectively, compared to MLP, with better performance at lower SNRs. UNET also outperformed MLP for predicting srNLLS MWF in the in vivo multiple‐sclerosis brain data, reducing mean absolute error over the whole brain by 61.9% and over the lesions by 67.5%. However, MLP yielded 41.1% and 51.7% lower mean absolute error for predicting in vivo NLLS MWF over the whole brain and the lesions, respectively, compared with UNET. The whole‐brain MWF processing time using a GPU was 0.64 seconds for UNET and 0.74 seconds for MLP. Conclusion: Subsecond whole‐brain MWF extraction from fast acquisition with spiral trajectory and T2 ‐prep data using UNET is feasible and provides better accuracy than MLP for predicting MWF output of srNLLS algorithm.